Congestion Control At ATM Multiplexers Using Neural Networks - APARNA S (2006)
INTERNAL GUIDE : Shantakumar B Patil . EXTERNAL GUIDE : Ram KumarP M USN No : 1MJ05SCS02 CARRIED OUT AT : Accent E Technologies (P) Ltd Bangalore ACC NO : PC45
Keywords: M.Teh Computer Science